A new species of Miroculis Edmunds, 1963 (Ephemeroptera: Leptophlebiidae) from Northeastern Brazil - Lima, Lucas R. C.; Raimundi, Erikcsen A.; Pinheiro, Ulisses; Salles, Frederico F. (Zootaxa, 2014)
Miroculis stenopterus, sp. nov., is described based on material from State of Pernambuco, Northeastern Brazil. The imago of the new species can be distinguished, among other characteristics, by an uncommon forewing shape, long and narrow, similar to species of genus Microphlebia. The tentatively associated nymph can be distinguished from other species of the genus mainly by the abdominal color pattern and the ratio of labial palp segment 2 to segment 1 (1.01–1.04 x).